Nucleophilic Additions of Organolithium Reagents to Heterocyclic Aldimines - Baek, Justin; Hoisington, Walker A.; Galgano, Evelyn S.; Schneider, Ethan H.; Barker, Timothy J. (Synlett, 2025)
The addition of alkyllithium reagents to heterocyclic aldimines is described. This method is a straightforward two-step procedure from the starting aldehyde and amine with one purification. The ability to use unprotected indole carboxaldehydes as substrates is a key feature of this method that makes it an attractive way to synthesize the corresponding amine products.
Keywords: alkyllithium; aldimine; indole; heterocycles; amine